(untitled) (Bangladesh Journal of Microbiology, 2020)
Cancer is one of the non-communicable lethal diseases which affects millions of people worldwide and is responsible for the majority of global deaths. Among the types of cancers occurring in humans, oral cancer has a higher incident rate which is significantly alarming. Oral cancer sites are associated with increased risk of metastasis, along with making the cancer site susceptible to infection by a vast number of opportunistic pathogens. Gram-negative opportunistic bacilli can dwell in these cancer ulcer sites since the patient becomes immune compressed due to radiotherapy and chemotherapy treatments, which prolong the infection. The present study was undertaken to find the most prevalent gram-negative bacilli in oral cavity cancer sites. Swab samples from 50 oral cancer patients were taken to check the presence of the opportunistic organisms. While the control group was set with people with no cancer, only 4 bacteria were isolated from 40 healthy volunteers. Among the isolates from both test group and control group, the most prevalent organism was Klebsiella species 37(45%), followed by Pseudomonas species 29 (34.5%) and Proteus species 8(9.5%). The least prevalent was Escherichia coli 5(6%). The isolates were all taken for antibiotic sensitivity testing (AST) against 15 antibiotics from 11 different groups used in hospitals. Results of the AST were as follows: 100% of the isolates from cancer patients were resistant to vancomycin, clindamycin, amoxicillin, penicillin G, and metronidazole. It was followed by azithromycin, where 86.25% of the isolates were resistant to it. The least resistance was seen against aminoglycoside antibiotic group, amikacin (6.25%), then gentamicin having a resistance percentage of 7.5. A substantial amount of qualitative data on medical history, clinical examination, and treatment, etc. was documented and presented in this study. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 85-90